Diagnosis and Treatment of Fungal Infections - Hospenthal, Duane R.; Rinaldi, Michael G. (Infectious Disease, 2015)
Diagnosis and Treatment of Fungal Infections, 2nd Edition is a thorough update to Diagnosis and Treatment of Human Mycoses.  Globally recognized experts are brought together again to provide the latest research and clinical evidence on fungal infections and basic mycology.  This concise text is divided into sections dedicated to the patient approach, laboratory and radiological diagnosis, antifungal agents, mycoses and instructive cases.  Ideal for patient care or as a teaching guide, the busy infectious disease, hematology, oncology, pulmonology, or critical care specialist will find this resource to be a practical tool for diagnosing, treating, and managing patients with fungal infections.